The true confessions of Charlotte Doyle - Avi, 1937- (New York : Avon, 1997)
Thirteen-year-old Charlotte Doyle, the only passenger on a voyage from England to America in 1832, must take serious matters into her own hands when she learns that the captain is murderous.
"A Richard Jackson book"--T.p. verso.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Book Links (A.L.A.), July 2009.
Booklist starred, July 2007.
Keywords: Historical fiction; Murder -- Fiction; Sea stories; Historical fiction; Homicide -- Fiction; Sea stories